Fluoropolymer solution for large protective film, large protective film, and large protective film
Patent Information
- Application Number
- CN202610349669.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-04-02
- Filing Date
- 2026-03-20
- Publication Date
- 2026-10-16
AI Technical Summary
[0014]即,在所述大型的防护薄膜制造中,虽然到目前为止以与LSI相同的水平选择并使用了溶媒,但由于使用的溶媒量也多,因此在制造成本方面存在大的课题
[0030] According to the present invention, by determining the solvent purity or boiling point range of a fluoropolymer solution for a large protective film with a wet film thickness of 30 μm and a dry film thickness of 2 μm to 10 μm coated and formed on a substrate, a large protective film with excellent appearance can be provided inexpensively.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to a large protective film used in a protective film for preventing foreign matter from adhering to a photomask used in the photolithography process of manufacturing flat panel displays, and more particularly to a fluoropolymer solution for a large protective film, a large protective film, and a large protective film. Background Technology
[0002] In the manufacturing of semiconductors such as large-scale integrated circuits (LSI) or flat panel displays, patterns are created by irradiating light onto the semiconductor wafer or flat panel display. However, if foreign matter is attached to the surface of the photomask or photomask used in this process, such foreign matter will absorb or scatter light, resulting in problems such as strain on the transferred pattern or unclear edges, and damage to size and quality.
[0003] Therefore, these operations are usually performed in cleanrooms, but even then, it is difficult to keep the photomask clean at all times. Thus, as a dust-proofing measure for the photomask surface, exposure is performed after a protective film is applied. In this case, foreign matter does not adhere directly to the photomask surface but rather to the protective film. Therefore, if the lens focus during photolithography is aligned with the patterned surface on the photomask, foreign matter on the protective film will be defocused and become irrelevant to the transfer.
[0004] Typically, a protective film is formed by attaching a transparent protective film containing highly transparent materials such as nitrocellulose, cellulose acetate, or fluoropolymer to the upper surface of a protective film frame made of materials such as aluminum, stainless steel, or polyethylene. Furthermore, an adhesive layer containing materials such as silicone resin or acrylic resin, for mounting on a photomask, and a release layer (partition) for protecting the adhesive layer are provided on the lower surface of the protective film frame.
[0005] Previously, the light source used in the photolithography process of flat panel display manufacturing was gamma rays (436 nm) and i rays (365 nm) from high-pressure mercury lamps. In the flat panel display manufacturing process, compared with semiconductor manufacturing processes, due to the large linewidth or spacing of the mask pattern, there is no need to use short-wavelength exposure light. In addition, due to the large exposure area and the required amount of exposure light, a wide-band exposure light with a wavelength range from i rays to gamma rays is used.
[0006] In recent years, in order to meet the further refinement of flat panel displays or new types of lithography, the development of lithography technologies using monochromatic exposure of i-rays or broadband light (deep ultraviolet (DUV)) in a shorter wavelength region than i-rays is being promoted.
[0007] In DUV exposure environments, protective films require high levels of light transmittance. Generally, amorphous fluoropolymers exhibit superior light transmittance in the ultraviolet region compared to many other polymer materials. Therefore, the technological development of large-scale protective films using amorphous fluoropolymers for flat panel displays is an urgent priority for the high-precision manufacturing of flat panel displays.
[0008] Manufacturing over 1000 cm 2 When preparing large protective films, the method often involves dissolving soluble polymer materials in a solvent and coating them onto a substrate in solution form. The same applies to amorphous fluoropolymers; however, fluorine-based materials exhibit extremely low intermolecular attraction or affinity with other compounds, resulting in a very limited selection of solvent components in the solution preparation of amorphous fluoropolymers.
[0009] Therefore, in most cases, fluoropolymer raw materials are obtained in solution form and used directly. Alternatively, the same solvent as that contained in the raw materials is used, and the concentration and viscosity are appropriately adjusted before being used in the manufacture of protective films.
[0010] Incidentally, in LSI protective films, the dry film thickness of the protective film is less than 1 μm. In this case, the wet film thickness of the polymer solution coated and formed on the substrate is also around 10 μm. Polymer solutions with this level of wet film thickness are extremely susceptible to drying due to environmental factors.
[0011] Specifically, localized drying begins with the low-boiling-point components in the polymer solution due to the movement of the substrate during the formation of the polymer solution layer (e.g., the movement of a substrate rotating at high speed when forming a protective film via spin coating) or downward flow within a cleanroom. Therefore, to achieve uniform drying within the substrate surface, solvents with purity or boiling points limited to a specific range have been investigated as the protective film solvents used. For example, obtaining a solvent pre-purified to a high purity is ideal. When this is not feasible, the solvent is purified by methods such as distillation or adsorption before use as the protective film solvent.
[0012] Manufacturing over 1000 cm 2 Large-scale protective films use a large amount of solvent, and the effort or cost required to refine this solvent is not negligible. However, to date, the solvents used in the manufacture of large-scale protective films are actually limited to solvents refined to the same high purity level as those used in LSI protective films.
[0013] Here, for those exceeding 1000 cm 2From the viewpoint of the physical strength of the film, the dry film thickness of such a large protective film is 2 μm to 10 μm. Similarly, the wet film thickness of the polymer solution coated and formed on the substrate during the manufacturing process is also 30 μm or more in the case of large protective films. For example, Patent Document 1 discloses that a fluoropolymer resin, which is the material of the protective film, is dissolved in a fluorinated solvent to form an 8% solution, and a protective film with a thickness of 4 μm is formed on an 850 mm × 1200 mm quartz glass substrate using a spin coater. In this case, the wet film thickness needs to be around 50 μm, and since it is produced by spin coating, a larger amount of solvent is conceivable.
[0014] That is, in the manufacture of the large protective film, although the solvent has been selected and used at the same level as LSI so far, there is a major issue in terms of manufacturing cost due to the large amount of solvent used.
[0015] [Existing Technical Documents]
[0016] [Patent Literature]
[0017] [Patent Document 1] Japanese Patent Application Publication No. 2006-323178 Summary of the Invention
[0018] [The problem the invention aims to solve]
[0019] The present invention was made in view of the above circumstances, and provides a fluoropolymer solution for large protective films, large protective films, and large protective films that can inexpensively produce large protective films with less film thickness unevenness and excellent appearance after solvent drying without having to select and use solvent at the same level as LSI as in the past.
[0020] [Technical means to solve the problem]
[0021] The inventors conducted extensive research to achieve the stated objective and discovered that in the manufacturing process of the protective film, the protective film polymer is used in a solution state. By optimizing the purity or boiling point range of the solvent in the solution used at this time, it is possible to provide large protective films with suppressed film thickness unevenness and excellent appearance at a lower cost, thus completing the present invention.
[0022] When the fluoropolymer solution used to coat and form the large protective film, which is the target of this invention, is applied to a substrate, there exists an optimal concentration or viscosity depending on the coating method or environment. If the concentration or viscosity is outside this optimal range, it is difficult to stably obtain a large protective film. On the other hand, differences in the purity or boiling point range of the polymer solution are generally not a problem in terms of the manufacturing process or the performance of the protective film as a product. This is because the solvent is completely removed during the manufacturing process and is not included in the protective film as a product. However, the inventors have found that in polymer solutions where the purity or boiling point range deviates from a specific range, it is impossible to manufacture large protective films with excellent appearance inexpensively.
[0023] Furthermore, the inventors have discovered that in manufacturing large protective films where the wet film thickness of the polymer solution formed on the substrate exceeds 30 μm, the required purity and boiling point range of the solvent are not the same as those for LSI protective films. Moreover, using a fluoropolymer solution with the same solvent level as LSI is not cost-effective for manufacturing large protective films. This is because, in cases where the wet film thickness of the polymer solution on the substrate is as thin as 10 μm, as in LSI protective films, even slight localized drying can cause significant deviations in solute concentration. This results in uneven film thickness after drying and deteriorates the appearance of the protective film. On the other hand, in the case of large protective films, even with the same degree of localized drying, because the wet film thickness of the polymer solution is 30 μm or more and there is a sufficient amount of solvent surrounding the solute, uneven film thickness does not occur.
[0024] Therefore, the present invention provides a fluoropolymer solution for large protective films, a large protective film, and a large protective film.
[0025] 1. A fluoropolymer solution for a large protective film, having an area of 1000 cm². 2 The polymer solution for protective films with fluoropolymers as the main component used in the above-mentioned large protective films is characterized in that, in the polymer solution with a wet film thickness of 30 μm or more and a dry film thickness of 2 μm to 10 μm coated and formed on the substrate, the purity of the main component used as the solvent is 80% or more.
[0026] 2. A fluoropolymer solution for a large protective film, having an area of 1000 cm². 2 The polymer solution for protective films with fluoropolymers as the main component used in the above-mentioned large protective films is characterized in that, in the polymer solution with a wet film thickness of 30 μm or more and a dry film thickness of 2 μm to 10 μm coated and formed on the substrate, the boiling point of the solvent used is within ±30°C.
[0027] 3. A large protective film with an area of 1000 cm² 2 The above-mentioned large protective film is made using the polymer solution according to 1 or 2.
[0028] 4. A large protective film obtained by stretching the protective film according to claim 3 onto the upper end face of a protective film frame.
[0029] [The effects of the invention]
[0030] According to the present invention, by determining the solvent purity or boiling point range of a fluoropolymer solution for a large protective film with a wet film thickness of 30 μm and a dry film thickness of 2 μm to 10 μm coated and formed on a substrate, a large protective film with excellent appearance can be provided inexpensively. Detailed Implementation
[0031] The present invention will now be described in detail.
[0032] This invention relates to a large-scale protective film used in large-scale protective films to prevent foreign matter from adhering to photomasks used in the photolithography process during the manufacturing of flat panel displays, etc. A large-scale protective film refers to a film with an area of 1000 cm². 2 The above protective film.
[0033] As materials for the protective film in this invention, amorphous fluoropolymers such as "CYTOP" manufactured by AGC, "Teflon (registered trademark) AF" manufactured by DuPont, and "Algoflon AD" manufactured by Solvay are used. In large-scale protective films, the film thickness is preferably 2 μm to 10 μm. If the film thickness is thinner than 2 μm, there is a tendency for problems such as the protective film cracking when foreign matter is removed by air purging due to reduced physical strength. On the other hand, if the thickness is thicker than 10 μm, there is a tendency for the price of the protective film product to increase due to increased film deflection caused by the film's own weight and increased amount of polymer used.
[0034] The protective film of the present invention is manufactured by at least the following steps: dissolving the protective film polymer in a solvent to prepare a polymer solution; uniformly coating the polymer solution onto a film-forming substrate; and heating and drying the substrate coated with the polymer solution.
[0035] First, the preparation process of the polymer solution for the protective film will be described. The polymer, which serves as the protective film material, is dissolved in various solvents. For the solvent used, in addition to having sufficient solubility to fully dissolve the fluoropolymer used as a raw material, it is preferable to select a compound with the highest possible boiling point, making drying at room temperature and pressure difficult. Furthermore, the concentration of the polymer solution can be arbitrarily set depending on factors such as the upper limit of the thickness of the wet layer that can be formed on the substrate, the target thickness of the dry film, and the optimal viscosity for the coating method.
[0036] The purity of the main component used as the solvent is 80% or higher, and more preferably in the range of 90% to 95%. If the purity is lower than 80%, the increased fluidity of the solution due to the drying of impurities will lead to a deterioration in the appearance of the protective film.
[0037] Furthermore, the boiling point range of the solvent, i.e., the difference between the highest and lowest boiling point values among the various solvents used, is preferably within ±30°C, more preferably within ±20°C, and even more preferably within ±10°C. When the boiling point value deviates from this range (i.e., the boiling point range of the solvent is wide), drying tends to be selectively performed starting from the lower boiling point components. Due to uneven drying, the appearance of the protective film tends to deteriorate.
[0038] Fluorinated solvents are preferred as the main component of solvents used to dissolve fluoropolymers. Specifically, examples include perfluorotributylamine (PFTBA), 1,1,2,2,3,3,4,4,4-nonafluoro-N,N-bis(nonafluorobutyl)butane-1-amine (PFTBA), and 1,1,1,2,2,3,4,5,5,5-decafluoro-3-methoxy-4-(trifluoromethyl)pentane. Specific trade names include "Fluorinert FC-75" and "Fluorinert FC-770" (both manufactured by 3M), "Galden DO2TS PFPE" (manufactured by Solvey), "CYTOP CT-SOLV100" and "CYTOP CT-SOLV180" (both manufactured by AGC), etc. Commercially available products of these compounds, or substances that have undergone multi-stage distillation purification to improve the purity of commercially available products or have had impurities removed by adsorbents, can be used as solvents. In the purification process, due to the high boiling point of the components used as protective film solvents, or their lack of affinity for adsorbents due to being fluorine compounds, not only is a large amount of time and effort required, but the yield also becomes a problem when high purity of the substance is required.
[0039] The prepared protective film is uniformly coated onto glass or other smooth substrates using polymer solutions via slit coating, spin coating, or similar methods. Spin coating is a process that uses centrifugal force to form a film by rotating a smooth substrate at high speed. While there are no particular restrictions on the type of coating machine, high uniformity of the coating film thickness is ideal. Furthermore, since the movement of the substrate during coating can affect the drying of the wet polymer film on the substrate, it is necessary to suppress substrate movement as much as possible, or to consider the air movement surrounding the wet film on the substrate.
[0040] Not only during coating but also shortly after coating, the wet layer on the substrate requires the same consideration. In a cleanroom environment, some of the solvent dries as it flows downwards. The solvent removed through drying begins with the low-boiling-point components. Due to localized drying points within the wet layer formed by coating, partial concentration of the solute occurs, leading to uneven film thickness and consequently a deterioration in the appearance of the protective film.
[0041] The solvent in the wet film formed on the substrate is completely removed during the process by heating. Heating methods include using a heating plate or oven, but in either case, heating to near the boiling point of the solvent or prolonged heating is preferred to prevent residual solvent from forming within the protective film. During heating, when the wet film thickness is 30 μm or more, drying patterns are generated due to heat convection within the wet film layer; therefore, it is also necessary to reduce the volume of the wet film by pre-drying or preheating.
[0042] Thus, using known methods, the protective film, which is a solid film formed on the substrate, is peeled off from the substrate to obtain a protective film as a self-standing film.
[0043] The protective film can be visually inspected under monochromatic inspection light. If uneven film thickness exists on the surface of the protective film, the degree of this unevenness can be observed by the difference in the degree of interference with the surrounding inspection light. For example, when using D-rays from a low-pressure sodium lamp as inspection light, the quality of the appearance described in this invention can be fully observed.
[0044] For example, the purity and boiling point (distillation range) of the fluorinated solvent, which is preferably used as the main component of the polymer solution for the protective film of the present invention, can be confirmed by manufacturer measurements or GC analysis. The main component of the solvent can be determined based on the Chemical Abstracts Service Registry Number (CAS No.) and gas chromatography-mass spectrometry (GC-MS).
[0045] The protective film of the present invention is obtained by conventional methods, by laying the protective film on the upper surface of the protective film frame via an adhesive layer for applying the protective film. Typically, an adhesive layer for applying a photomask is provided on the lower surface of the protective film frame, and a release layer is further applied thereon in a peelable manner.
[0046] The protective membrane frame can be made of any known material, but if deformation is a concern, overly soft materials cannot be used. It can also be made of steel, such as stainless steel, but lightweight aluminum alloys, such as those conforming to Japanese Industrial Standards (JIS) A7075, JIS A6061, and JIS A5052, are preferred.
[0047] The surface of the protective membrane frame is typically roughened by sandblasting or chemical polishing, but this invention does not impose any limitations on the roughening method. For example, when using aluminum, the surface can be sandblasted with stainless steel, corundum, glass beads, etc., and then roughened by chemical polishing based on NaOH, etc. Anodizing of the protective membrane frame surface can be performed by known methods, but is usually carried out in an acidic electrolyte. Commonly used acidic electrolytes include aqueous solutions of sulfuric acid and oxalic acid.
[0048] Furthermore, the adhesive layer for attaching the protective film is formed by diluting it with a solvent as needed, applying it to the upper surface of the protective film frame, heating it, and then drying and hardening it. Methods for applying the adhesive include brushing, spraying, and using an automatic dispensing machine. On the other hand, regarding the mask adhesive protective pad, various known materials can be used, such as polyethylene terephthalate (PET), polytetrafluoroethylene (PTFE), perfluoroalkoxyalkane (PFA), polyethylene (PE), polycarbonate (PC), vinyl chloride, and polypropylene (PP), forming a release layer suitable for the adhesive used on the surface of these substrates.
[0049] [Example]
[0050] The following examples illustrate the present invention in detail, but the present invention is not limited to the following examples.
[0051] [Examples 1-3, Comparative Examples 1-3]
[0052] Prepare 850 mm × 1200 mm synthetic quartz glass, clean its surface by dry cleaning, and use it as the film-forming substrate for forming the protective film. Prepare a solid form of the product name "CYTOP" (CTX-809SP2, manufactured by AGC), and prepare perfluorotributylamine (PFTBA) adjusted to various purities as shown in Table 1. Dissolve the solid form of the fluoropolymer in the various solvents shown in Table 1 to prepare polymer solutions of 7 wt%.
[0053] The solvents in Table 1 are explained in detail below. Solvent A is product name "FC-43" (manufactured by 3M, CAS No. 311-89-7), which, even without further refining, contains over 95% PFTBA. Its boiling point range is 165℃ to 185℃. Solvent B is product name "WB170" (manufactured by Bright Chemical, CAS No. 311-89-7), with a PFTBA purity of less than 80%. It also contains low-boiling-point components and has a boiling point range of 145℃ to 185℃. Solvent C is a distillate of Solvent B, a substance from which low-boiling-point components have been removed, and a PFTBA purity refined to 84%. Solvent D is a mixture of Solvent A and Solvent B, a mixed solvent containing 92% PFTBA. Solvent E is a mixture of solvent A and a product called "Novec 7300" (manufactured by 3M) that can dissolve CYTOP. The PFTBA ratio is 74%, and the boiling point range is 98℃~185℃.
[0054] The fluoropolymer solutions dissolved in the solvents listed in Table 1 were pumped and fed into a 0.2 μm diameter membrane filter. The filtered liquid was then uniformly coated onto the film-forming substrate using a slit-die coating method, with a wet film thickness of 31 μm and a dry film thickness of 2.2 μm (Examples 1-3 and Comparative Examples 1 and 2), or a wet film thickness of 12 μm and a dry film thickness of 0.83 μm (Comparative Example 3). After air drying for at least 2 hours, the film was dried in an infrared oven at 200°C for 20 minutes. Finally, the protective film was peeled off using a temporary frame.
[0055] The protective film was visually inspected under low-pressure sodium lamp (product name "NX180" manufactured by Iwasaki Electric Co., Ltd.), and film thickness unevenness was observed. The results of the observation are shown in Table 1 below.
[0056] [Table 1]
[0057]
[0058] Based on the observations, even when using solvents C and D (PFTBA purity 84% and 92%, boiling point range 165–185°C), a protective film with an appearance no less impressive was obtained compared to the case using solvent A with the highest purity.
[0059] On the other hand, in solvents with low PFTBA purity, such as solvent B (Comparative Example 1), the appearance deteriorated due to increased fluidity of the solution caused by the drying of impurity components.
[0060] Furthermore, in cases where the boiling point range of a solvent, such as solvent E (Comparative Example 2), is significantly wider, a tendency to selectively dry starting from the low-boiling-point components was observed, and a tendency for the film appearance to deteriorate due to uneven drying was also observed.
[0061] Furthermore, in a self-standing membrane (Comparative Example 3) prepared using solvent D (PFTBA purity 92%) with a wet film thickness of 12 μm and a dry film thickness of 0.83 μm, uneven film color was observed on the surface of the obtained self-standing membrane under monochromatic light. This confirms that, as is known, a high-purity solvent with a purity of 95% or higher is required in regions with thin wet films.
[0062] Based on the above, from the point of view of manufacturing rationality, in the manufacture of large protective films, setting the solvent in the polymer solution to a purity range of 80% or more, preferably 90% to 95%, and setting the boiling point range of the main solvent component to ±30°C, preferably within ±20°C, can result in obtaining large protective films with excellent appearance at a lower cost.
Claims
1. A fluoropolymer solution for a large protective film, having an area of 1000 cm². 2 The polymer solution for the above-mentioned large-scale protective films, which is mainly composed of fluoropolymers, is characterized in that... In a polymer solution with a wet film thickness of 30 μm or more and a dry film thickness of 2 μm to 10 μm, the purity of the main component used as the solvent is 80% or more.
2. A fluoropolymer solution for a large protective film, having an area of 1000 cm². 2 The polymer solution for the above-mentioned large-scale protective films, which is mainly composed of fluoropolymers, is characterized in that... In polymer solutions with a wet film thickness of 30 μm or more and a dry film thickness of 2 μm to 10 μm that are coated and formed on a substrate, the boiling point of the solvent used is within ±30°C.
3. A large protective film with an area of 1000 cm² 2 The above-mentioned large protective film is made using the polymer solution as described in claim 1 or 2.
4. A large protective film obtained by stretching the protective film as described in claim 3 onto the upper end face of a protective film frame.
Citation Information
Patent Citations
Pellicle for lithography, and its manufacturing method
JP2006323178A